IMPLEMENTASI KEBIJAKAN PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI KABUPATEN TRENGGALEK - Chusniati, Siti (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
Water is a basic need for mankind, but the fact remains that not everyone has access to clean water and healthy adequately, in accordance with its needs. The issue of water and poor sanitation in Indonesia spawn Program Pamsimas. The goal of the Program is to improve the access of Pamsimas drinking water and sanitation for the poor in rural areas and suburbs, as well as enhancing the values and behaviors of healthy living by building/infrastructure and means of providing drinking water and sanitation sustainable community-based and can be adopted by people to achieve the MDGs targets. Based on the results of the study and discussion of the two issues that the formulation is specified, then the obtained results, among other Policy Implementation Program Pamsimas in Trenggalek already running in accordance with the technical guidelines which in practice already refers to the components of the program i.e., community empowerment, the Ministry of sanitation, drinking water supply, and support the management of the commissioning programme. Factors that support the success of the Program Pamsimas in the presence of, among others, Trenggalek Regency method involving the existence of community empowerment, providing innovation and creativity inspires the citizens through group work, compromise bottom up and top down and commitment at all levels. Factors that impede the success of Trenggalek Regency Pamsimas, among others, lack of cooperation, natural condition, as well as the quality of the water resources untapped.